Assesment of Serum Magnesium Level in Postmenopausal Women With Osteoporosis - Marjan Mahdavi Roshan; Maryam Khazdooz; Parizad Jaraghijoo; Mehrangiz Ebrahimi Mamaghani (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: This study was designed to assess nutritional and biochemical factor of magnesium in postmenopausal osteoporotic women. Methods & Materials: The population of this analytical cross- sectional study, was 60 postmenopausal osteoporotic women ,referred to rheumateology clinic of Tabriz. Nutritional intake was determined by 3 day food recall and food frequency questionnaire، individual and clinical information by questionnaire and weight and height of subjects were measured by scale. Serum magnesium concentration was measured by atomic absorption spectrophotometer. Data were analyzed using analytical and descriptive statistical methods. Results: Mean age of women were 58.85 years old .Mean of energy and protein intake from diet was 1876 kcal, 53.3 g/day,respectively.The mean intake of magnesium from diet was 120 mg/day that was significantly lower than recommended dietary allowance (P<0.05) (37%RDA). Mean of magnesium serum concentration in this patients was 0.7±0.01 mmol/L that was in less normal ranges.The correlation between magnesium intake and age was significantly negative. Conclusion: Base on this study finding ,magnesium status in women with postmenopausal osteoporosis was not siutable considering the significant correlation between magnesium intake and bone mineral density and important role of magnesium on bone metabolism, nutritional education to intake magnesium rich foods, is suggested for maintanence of bone density.